The international handbook of corporate finance - Terry, Brian J. (Chicago : Glenlake Pub. Co. ; London : Fitzroy Dearborn, 1997)
Provides coverage on subjects ranging from the most established principles in corporate finance to recent innovations. This text should be of interest to those coming to these concepts for the first time as well as professionals. Topics covered include the principles of lending.
Includes index.
oif 27/03/15, nmn 06/05/15
Loan
Keywords: Corporations -- Finance